Association of methylenetetrahydrofolate reductase C677T polymorphism with the pre-eclampsia risk in Hakka pregnant women in Southern China. (2nd April 2020) - Hou, Jingyuan; Lin, Lifang; Guo, Wei; Luo, Dandan; Lan, Liubing
Abstract: The aim of this study is to clarify the possible association between methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and pre-eclampsia in Hakka pregnant women in southern China. Pre-eclampsia and normal pregnant women were consecutively collected and MTHFR C677T genotypes were determined by the DNA sequencing method. One hundred and thirteen pre-eclampsia patients were CC homozygote (113 of 191, 59.2%), 68 of 191 (35.6%) were CT heterozygote, and 10 of 191 (5.2%) were TT homozygote, with the frequency of the T allele equal to 0.77. This is in comparison with the normal control group where 106 of 202 (52.5%) were CC homozygote, 83 of 202 (41.1%) were CT heterozygote, and 13 of 202 (6.4%) were TT homozygote, with the frequency of the T allele equal to 0.27. No statistically significant differences were observed in genotype or allele frequencies between the pre-eclampsia and normal control for the C677T polymorphism of MTHFR gene ( p > .05). The findings of this study suggest that polymorphisms of MTHFR C677T genes were not associated with pre-eclampsia in Hakka pregnant women from southern China, but additional studies are necessary to explore the mechanisms involving it.